2022
DOI: 10.1038/s41598-022-18333-2
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic branch stability is mediated by non-enzymatic functions of MEC-17/αTAT1 and ATAT-2

Abstract: Microtubules are fundamental elements of neuronal structure and function. They are dynamic structures formed from protofilament chains of α- and β-tubulin heterodimers. Acetylation of the lysine 40 (K40) residue of α-tubulin protects microtubules from mechanical stresses by imparting structural elasticity. The enzyme responsible for this acetylation event is MEC-17/αTAT1. Despite its functional importance, however, the consequences of altered MEC-17/αTAT1 levels on neuronal structure and function are incomplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Conversely, this ratio was found to increase in the shaft of stretched axons, highlighting the presence of more stable MTs ( Takemura et al, 1992 ; Cappelletti et al, 2021 ). A correlation between the acetylation of MTs and their stabilization has always been observed in various studies on neurons ( Morley et al, 2016 ; Yan et al, 2018 ; Teoh et al, 2022 ), as well as in other studies on non-neuronal models ( Swiatlowska et al, 2020 ; Coleman et al, 2021 ). Consistently, in previous works we found that the force-induced stabilization of the MTs in the shaft causes their accumulation in stretched axons ( De Vincentiis et al, 2020 , 2023 ; Falconieri et al, 2023b ).…”
Section: Discussionmentioning
confidence: 54%
“…Conversely, this ratio was found to increase in the shaft of stretched axons, highlighting the presence of more stable MTs ( Takemura et al, 1992 ; Cappelletti et al, 2021 ). A correlation between the acetylation of MTs and their stabilization has always been observed in various studies on neurons ( Morley et al, 2016 ; Yan et al, 2018 ; Teoh et al, 2022 ), as well as in other studies on non-neuronal models ( Swiatlowska et al, 2020 ; Coleman et al, 2021 ). Consistently, in previous works we found that the force-induced stabilization of the MTs in the shaft causes their accumulation in stretched axons ( De Vincentiis et al, 2020 , 2023 ; Falconieri et al, 2023b ).…”
Section: Discussionmentioning
confidence: 54%
“…Conversely, this ratio was found to increase in the shaft of stretched axons, documenting the presence of more stable MTs (Takemura et al, 1992; Cappelletti et al, 2021). In general, an increase in acetylation of MTs, with a consequent increase in stability, has been always observed in various studies on neurons (Morley et al, 2016; Yan et al, 2018; Teoh et al, 2022), as well as in other work on non-neuronal models (Swiatlowska et al, 2020; Coleman et al, 2021). We found in previous works that the stabilization of the MTs in the shaft causes their accumulation in the axon (De Vincentiis et al, 2020, 2023; Falconieri et al, 2023).…”
Section: Discussionmentioning
confidence: 67%
“…Optimum levels of MEC-17 and ATAT-2 are needed for the temporal control of synaptic branching. Overexpression or loss of these enzymes causes a delay in synaptic branching and impaired synaptic formation in mechanosensory neurons of Caenorhabditis elegans [ 141 ]. Neuronal cells with defective elongators show a drastic reduction of acetylated α-tubulin.…”
Section: Ptms Of Tubulin – Limelight On Acetylationmentioning
confidence: 99%
“…Biochemical analyses of tubulin deacetylation via HDAC6 revealed its strong preference for tubulin dimers to assemble MTs. Although HDAC6 is believed to deacetylate the K40 residue of α-tubulin, quantitative mass spectrometry studies revealed K60, K370, and K394 on α-tubulin as well as K58, K103, and K154 on β-tubulin as newer putative sites of HDAC6-mediated deacetylation [ 141 ]. A previous study showed that increased MT acetylation via HDAC6 inhibition leads to the recruitment of molecular motors kinesin-1 and cytoplasmic dynein to MTs, thereby increasing the MT-dependent corticostriatal transport of BDNF [ 137 ].…”
Section: Ptms Of Tubulin – Limelight On Acetylationmentioning
confidence: 99%